2020
DOI: 10.1002/jcp.29457
|View full text |Cite
|
Sign up to set email alerts
|

E35 ablates acute leukemia stem and progenitor cells in vitro and in vivo

Abstract: Leukemia stem cells (LSCs) have critical functions in acute leukemia (AL) pathogenesis, participating in its initiation and relapse. Thus, identifying new molecules to eradicate LSCs represents a high priority for AL management. This work identified E35, a novel Emodin derivative, which strongly inhibited growth and enhanced apoptosis of AL stem cell lines, and primary stem and progenitor cells from AL cases, while sparing normal hematopoietic cells. Furthermore, functional assays in cultured cells and animals… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…Peripheral whole blood samples were obtained at patients’ scheduled visits after disease diagnosis. Peripheral blood mononuclear cells (PBMCs) were isolated according to the procedures we previously reported ( 24 26 ). For platelet preparation, venous blood was obtained by venipuncture into EDTA-based anticoagulant tubes.…”
Section: Methodsmentioning
confidence: 99%
“…Peripheral whole blood samples were obtained at patients’ scheduled visits after disease diagnosis. Peripheral blood mononuclear cells (PBMCs) were isolated according to the procedures we previously reported ( 24 26 ). For platelet preparation, venous blood was obtained by venipuncture into EDTA-based anticoagulant tubes.…”
Section: Methodsmentioning
confidence: 99%
“…synthesized another class of emodin quaternary ammonium salt derivatives, and identified E35 (BrNO5·H2O) as a potential therapeutic candidate for hematologic cancers with higher aqueous solubility and specificity than emodin. E35 efficiently suppressed growth and enhanced apoptosis of various acute leukemia stem and progenitor cells, including but not limit to HL-60, Molt-4, and CA46, by markedly downregulating the drug-resistant genes like MDR1, MRP1, TOPIIβ , GSTπ, and BCL-2 , and dramatically blocking AKT/mTOR pathway [ 205 ].…”
Section: Modification Of Emodin For Better Therapeutic Potentialmentioning
confidence: 99%
“…We also found that emodin induces apoptosis in resistant acute leukemia cells [ 7 ]. One emodin derivative, Emodin 35 (E35, C 34 H 50 BrNO 5 ·H 2 O; molecular weight, 631.29; Figure 1(a) ), has been shown to downregulate TP53 protein expression and decrease PI3K/Akt protein phosphorylation in diffused large B cell lymphoma cells [ 8 ] while downstreaming Crk, Akt/mTOR, and MEK/ERK pathways in 32Dp210-T315I leukemia cells [ 9 ], inhibiting the cellular growth, and inducing apoptosis in leukemia cells [ 10 ]. By far, most studies focused on the effects of emodin on leukemia, and only limited studies investigated the effects of emodin on MM.…”
Section: Introductionmentioning
confidence: 99%